Monitoring Keamanan Toko Menggunakan Sensor Pir dan Pintu Berbasis Arduino dengan Notifikasi SMS Gateway - Putra, Jaka; Sumarno, Sumarno; Damanik, Bahrudi Efendi; Hartama, Dedy; Gunawan, Indra (Building of Informatics, Technology and Science (BITS), 2019)
The author has conducted research at UD Stores. Variant Jl. Kabu-Kabu No. 31 Pematangsiantar and found a problem where the theft was prone to the place and no employees guarded the store during the closing. Then another problem arises how to monitor stores from a distance by using SMS Gateway notifications. So here the author provides a solution so that the store can be monitored remotely with SMS Gateway Notifications. The author implements a Magnetic switch on the front door so that when the door is forced open the buzzer will ring and the owner receives an SMS, then in the front room the writer implements a PIR sensor where when a human passes the sensor the buzzer will turn on and the shop owner will get SMS notification.